(untitled) (Altre Modernità, 2022)
I would like to analyze a specific case of Shakespearean prison theatre. Un’isola. Dalla mia finestra si vedono le montagne (2018) is a rewriting of The Tempest by director Alessia Gennari, performed by an international cast consisting of some inmates of the prison of Vigevano (PV). A selection of the Shakespearean lines, translated into Italian, are accompanied by short sections composed directly by the inmates and by linguistic and cultural elements of diverse origin. In a total institution where the role of the prisoners is flattened on the conventional one of the criminal, the creative activity in the theatrical field allows to develop forms of resilience in the construction of stratified identities. Vulnerability can also be explored, even though it might be perceived as divergent from the condition of guilt. In this dimension, Shakespeare becomes the filter through which long unheard voices find the way to express themselves. At the same time, the text of The Tempest assumes the function of ‘pre-text’, at the service of the prison and the prisoners themselves. Between Shakespeare’s authority and the agency of the marginalized subjects, a stratified relationship is established, on whose declinations in dramaturgical and performative practice I would like to focus my attention.